THE EFFECT OF DIFFERENT COMBINATIONS OF CALCIUM HYDROXIDE FOR MANAGEMENT OF POST-OPERATIVE PAIN IN ACUTE APICAL PERIODONTITIS - Yousaf, Ajmal; Ali, Fatima; Bibi, Afshan; Ahmed, Ahsan Masood; Ashfaq, Sana; Zahra, Syeda Fatima Tu (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find the effect of different combinations of Calcium Hydroxide for the management of post-operative pain in acute apical periodontitis.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Operative Dentistry Armed Forces Institute of Dentistry, Rawalpindi. from Jun to Nov 2019.Methodology: A total of 282 patients presenting with acute apical periodontitis in their mandibular posterior teeth were selected for this study and were randomly divided into three equal groups with the help of scientific random number table. Group-A patients were given intracanal dressing of Calcium Hydroxide mixed with Chlorhexidine, group-B patients were given intracanal dressing of Calcium Hydroxide mixed with Saline and group-C patients were given intracanal dressing of Calcium Hydroxide mixed with Dexamethasone. Endodontic therapy was initiated after application of rubber dam, following pulpectomy and disinfection with frequent irrigation, canals were prepared and intra-canal dressings were placed according to the allotted group and the cavity was restored till the next appointment. Post-operative pain was recorded at 24 hours, 48 hours and one week using the visual analogue scale.Results: The three intra-canal combinations of Calcium Hydroxide used in the study were found to be equally effective in reducing pain. Overall, the result between the three groups after 24 hours proved to be insignificant (p=0.40), after 48 hours (p=0.84) and 1 week (p=0.45) were also insignificant.Conclusion: Calcium Hydroxide mixed with Saline, Chlorhexidine and Dexamethasone are all effective for pain reduction with dexamethasone being the most effective.